STUDENTS’ PERCEPTIONS OF USING ROLE-PLAY TECHNIQUES IN LEARNING ENGLISH - Engelina Salainti; Andi Hamzah Fansury (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study investigated students’ perceptions of using the role-play technique in learning English. The research method employed was a descriptive study with a qualitative approach, involving some students in basic English general classes in the 2025/2026 academic year as participants in this research. Data was gathered through questionnaires focused on the students' experiences and perceptions during the implementation of the role-play technique in English class. The result showed that the majority of students felt an improvement in their motivation and ability to speak in English through this technique. Furthermore, role-play is effective in creating a learning environment that becomes more interactive and enjoyable. Therefore, it supports the English learning process communicatively. This study recommended the implementation of role-play as one of the strategies that improve students’ engagement and learning outcomes.